The Influence of Contextual Teaching and Learning Models on Learning Outcomes of Class V Students UPTD SD NEGERI 122337 Pematang Siantar T.A 2023/2024 - Meri Christina Sitanggang; Lisbet Novianti Sihombing; Fine Eirene Siahaan (MultiTech Publisher, 2023)
This research aims to determine whether there is an influence of the Contextual Teaching and Learning Model on the learning outcomes of class V students at UPTD SD Negeri 122337 Pematang Siantar FY 2023/2024. The method in this research is a quantitative experimental type method whose research design is Pre-experimental type one group pretest -posttest. Conducted in September 2023, the population of all students at UPTD SD Negeri 122337 Pematang Siantar and a sample of 28 students consisting of 14 female students and 14 male students used was purposing sampling with two research variables: the dependent variable (x) in the form of learning outcomes, as well as the independent variable (y) in the form of the Contextual Teaching and Learning model, a learning concept that helps teachers link the material taught with students' real world situations which encourages students to make connections between the knowledge they have and its application in their daily lives. Data collection techniques are test techniques with validity tests, reliability tests, difficulty level tests, and differentiating power tests. The test results using the N-gain technique with the help of the SPSS version 21 program, based on the calculation results obtained a mean of 0.6726, that the effectiveness is 0.7 > 0.6726 > 0.3 which is included in the medium category, in the ANOVA test the significant value is 0.000, which is where 0.000 < 0.05 then Ho is rejected and Ha is accepted. This means that all independent variables have a significant influence on the dependent variable. So it can be concluded that there is an influence of the Contextual Teaching and Learning model on the learning outcomes of class V students at UPTD SD Negeri 122337 Pematang Siantar FY 2023/2024.